2016
DOI: 10.1016/j.neo.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

ATP-Dependent Lon Protease Contributes to Helicobacter pylori-Induced Gastric Carcinogenesis

Abstract: Helicobacter pylori infection is the strongest risk factor for development of gastric cancer. Host cellular stress responses, including inflammatory and immune responses, have been reported highly linked to H. pylori-induced carcinogenesis. However, whether mitochondrial regulation and metabolic reprogramming, which are potently associated with various cancers, play a role in H. pylori-induced gastric carcinogenesis is largely unknown. Here we revealed that Lon protease (Lonp1), which is a key inductive of mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…H. pylori -induced HIF-1α expression is associated with increased expression of Mcl-1, VEGF and Lon protease, via a transcriptional mechanism (Bhattacharyya et al, 2010; Kang et al, 2014; Luo et al, 2016). However, in our hands, we found little evidence for enhanced transcription of typical target genes due to HIF-1α (see Figures 4, 5), despite the notable increase in HIF-1α protein levels and reporter activity (Figure 1C).…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori -induced HIF-1α expression is associated with increased expression of Mcl-1, VEGF and Lon protease, via a transcriptional mechanism (Bhattacharyya et al, 2010; Kang et al, 2014; Luo et al, 2016). However, in our hands, we found little evidence for enhanced transcription of typical target genes due to HIF-1α (see Figures 4, 5), despite the notable increase in HIF-1α protein levels and reporter activity (Figure 1C).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, Hp-infected gastric epithelial cells have exhibited increased glycolysis and increased expression of Lon protease 1 (Lonp1), a protein that activates the mitochondrial unfolded protein response and maintains mitochondrial function. Correspondingly, knockdown of Lonp1 has been shown to reverse alterations in metabolism that are caused by Hp,4 thereby suggesting that aerobic glycolysis and mitochondrial dysfunction correlate with the genesis of GC. Hp-induced GC is also characterized by higher expression levels of the M2 isoform of pyruvate kinase, PKM2, among other factors that are induced in GC and that affect mitochondrial function 5,6.…”
Section: Helicobacter Pylori Promotes the Genesis Of Gc By Inducing Mmentioning
confidence: 99%
“…Many studies found that H. pylori can metabolize glucose by both oxidative and fermentative pathways 49 – 53 . H. pylori infected gastric epithelial cells have exhibited increased glycolysis and increased expression of Lon protease 1 (Lonp1), Lonp1 is a key regulator of metabolic reprogramming in H. pylori -induced gastric carcinogenesis 54 , 55 . We also identified two immune-related pathways, including antigen-processing and presentation pathway as well as autoimmune thyroid disease pathway.…”
Section: Discussionmentioning
confidence: 99%